Financial access of midstream agricultural firms in Africa: Evidence from the LSMS‐ISA and World Bank Enterprise Surveys - Ambler, Kate; de Brauw, Alan; Herskowitz, Sylvan; Pulido, Cristhian (Wiley, 2024)
We use data from the Living Standards Measurement Study—Integrated Surveys on Agriculture and the World Bank Enterprise Survey from seven African countries, to identify agricultural midstream firms and assess their access to credit, comparing them to nonagricultural midstream firms. We find that the agricultural midstream firms are larger and more productive, and are less likely to report barriers to accessing credit, although overall access levels remain low. These findings help build our understanding about the financial needs of micro-, small-, and medium-size enterprises in the agricultural midstream and suggest that more targeted data collection could further this research agenda.